Dos textos das pirâmides aos textos dos sarcófagos: a democratização da imortalidade como um processo sócio-político - João, Maria Thereza David (2008)
The central issue of this work is the Egyptian thought about death, with emphasis laying on the analysis of mortuary literature Pyramid Texts and Coffin Texts. The usurpation, by private individuals, of texts once intended to offer immortality for the king, is known by the Egyptologists as democratization of immortality. It is this particular process which interests more precisely to our goals within this dissertation. It has been intended to study the funerary religion of ancient Egypt in a socio-political perspective, taking on account the mutual relationships established between religion and society, by analyzing the social, political and economical events that took place at the end of Old Kingdom (2686 - 2160 A.C.), which culminated in an anarchic era called the First Intermediate Period (2160 - 2055 A.C ).